The challenging management of borderline ovarian tumors (BOTs) in women of childbearing age - Della Corte, Luigi; Mercorio, Antonio; Serafino, Paolo; Viciglione, Francesco; Palumbo, Mario; De Angelis, Maria Chiara; Borgo, Maria; Buonfantino, Cira; Tesorone, Marina; Bifulco, Giuseppe; Giampaolino, Pierluigi (Frontiers in Surgery, 2022)
Borderline ovarian tumors (BOTs) account for approximately 15% of all epithelial ovarian cancers. In 80% of cases the diagnosis of BOTs is done at stage I and more than a third of BOTs occurs in women younger than 40 years of age wishing to preserve their childbearing potential; the issue of conservative surgical management (fertility-sparing treatment) is thus becoming of paramount importance. At early stages, the modalities of conservative treatment could range from mono-lateral cystectomy to bilateral salpingo-oophorectomy. Although cystectomy is the preferred method to promote fertility it can lead to an elevated risk of recurrence; therefore, an appropriate counseling about the risk of relapse is mandatory before opting for this treatment. Nevertheless, relapses are often benign and can be treated by repeated conservative surgery. Besides the stage of the disease, histological subtype is another essential factor when considering the proper procedure: as most mucinous BOTs (mBOTs) are more commonly unilateral, the risk of an invasive recurrence seems to be higher, compared to serous histotype, therefore unilateral salpingo-oophorectomy is recommended. In the appraisal of current literature, this review aims to gain better insight on the current recommendations to identify the right balance between an accurate staging and an optimal fertility outcome.